Neurodevelopmental outcome after neonatal perforator stroke. (26th July 2015) - Ecury‐Goossen, Ginette M; van der Haer, Marit; Smit, Liesbeth S; Feijen‐Roon, Monique; Lequin, Maarten; de Jonge, Rogier C J; Govaert, Paul; Dudink, Jeroen
Abstract : Aim: To assess outcome after neonatal perforator stroke in the largest cohort to date. Method: Survivors from a cohort of children diagnosed with neonatal perforator stroke using cranial ultrasound or magnetic resonance imaging were eligible for inclusion. Recovery and Recurrence Questionnaire score, presence of cerebral palsy (CP), and crude outcome were assessed, specifically (1) the ability to walk independently, (2) participation in regular education, and (3) the presence of epilepsy. Results: Thirty‐seven patients (20 males, 17 females) aged 3 to 14 years (mean age 8y) were included in the study: 14 with isolated single perforator stroke, four with multiple isolated perforator strokes, and 19 with additional brain injury. Out of 18 children with isolated perforator stroke(s), four had CP, one could not walk independently, and one developed epilepsy. The posterior limb of the internal capsule was involved in four out of 18 patients; three of these patients had CP. Of 19 children with additional brain injury, 11 had CP and three were not able to walk independently. Three out of nine children with concomitant cortical middle cerebral artery stroke developed epilepsy. Interpretation: Perforator stroke patterns can be of use in predicting long‐term outcome and for guiding counselling and surveillance. Motor outcome was favourable in children with isolated perforator stroke(s), except when the posterior limb of the internal capsule was involved. What this paper adds: Motor outcome is favourable in children with isolated neonatal perforator stroke(s), except when posterior limb of the internal capsule is involved. In children with isolated neonatal perforator stroke(s), motor outcome is more favourable than in those with concomitant brain injury. Childhood epilepsy is rare in children with isolated neonatal perforator stroke. This article is commented on by Kirton on pages8–9 of this issue.